Optimizing Seedling Media for Tomato (Lycopersicum esculentum Mill.) Cultivation - Saptorini, Saptorini; Supandji, Supandji; Widiyono, Wahyu; Tafakresnanto, Chendy; Sari, Intan Permata; Putra, Niko Prismanda (Kadiri University - Faculty of Agriculture, 2025)
This study evaluates the growth performance and cost-effectiveness of six different seedling media for tomato (Lycopersicum esculentum Mill) cultivation: sand (M1), rice husk charcoal (M2), clay (M3), organic fertilizer (M4), clay-organic fertilizer (M5), and sand-organic fertilizer (M6). The experiment assessed plant height, number of leaves, and number of branches from 7 to 35 days after sowing (DAS). Results showed that media containing organic fertilizer (M4, M5, M6) significantly enhanced all growth parameters compared to non-organic treatments. Among these, M5 (clay-organic fertilizer) achieved the highest values for plant height (34.9 cm), number of leaves (15.5), and number of branches (5.5) at 35 DAS, indicating superior performance. However, cost analysis revealed that M5 also incurred the highest production cost. In contrast, M6 (sand-organic fertilizer) offered a more cost-effective option by providing strong growth performance at a lower cost. These findings highlight the importance of incorporating organic fertilizers into seedling media to improve early growth stages of tomato plants. The use of organic blends, particularly M6, presents a practical and sustainable solution for smallholder farmers aiming to maximize seedling vigor without incurring high input costs, ultimately supporting more efficient and eco-friendly agricultural practices.